C-Band Vivaldi Antenna and Its Array - Shukla, Saurabh; Upadhyay, Naveen; Sharma, Sandhya; Hemrajani, Naveen (Asian Journal of Engineering and Applied Technology, 2013)
A novel Vivaldi Antenna has been designed for IEEE C-band i.e. 4-8 GHz. The objective of the design is to achieve return loss better than -10 dB over the entire frequency range with a moderate gain ranging from 4-9 dB. The minimum half power beamwidth required in both Azimuth and Elevation planes is 500 so that designed Vivaldi Antenna element can be used for wide angle scanning. The designed antenna has been fed by a stripline that helps in efficient coupling of microwave power to slotline. The triplicate structure of Vivaldi Antenna helps in reducing the spurious radiations from stripline feed. A 5×1 H-plane C-Band Vivaldi Antenna array has been designed to find out the effect of array environment on the characteristics of Vivaldi Antenna. All the designs, simulations and analysis have been done in CST Microwave Studio 2011.